1991
DOI: 10.1002/j.1460-2075.1991.tb07842.x
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase II induces c-fos expression via the serum response element pathway and p67SRF phosphorylation in living fibroblasts.

Abstract: Elevation of intracellular casein kinase II (CKII) levels through microinjection of purified CKII results in the rapid and transient induction of c‐fos in quiescent rat embryo fibroblasts, and activation of quiescent cells by serum is accompanied by the nuclear relocation of endogenous CKII. The induction of c‐fos by CKII is inhibited by coinjection of oligonucleotides corresponding to the sequence of the serum response element (SRE) present in the c‐fos promoter, indicating that competitive displacement of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…In contrast, nucleolin is constantly present in the nucleoli but highly phosphorylated in growing cells and dephosphorylated in confluent cells (23). ln line with these data, several authors described that CK2, or especially its ␤ subunit, was located mainly in the nucleus of growing cells but spread throughout cells that are serumstarved or confluent (16,17,40). Therefore, a coordinated spatiotemporal distribution of FGF-2 and CK2 in the nucleus could allow the regulation of specific nuclear protein phosphorylations, such as nucleolin phosphorylation during the G 1 /S transition.…”
Section: Figmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast, nucleolin is constantly present in the nucleoli but highly phosphorylated in growing cells and dephosphorylated in confluent cells (23). ln line with these data, several authors described that CK2, or especially its ␤ subunit, was located mainly in the nucleus of growing cells but spread throughout cells that are serumstarved or confluent (16,17,40). Therefore, a coordinated spatiotemporal distribution of FGF-2 and CK2 in the nucleus could allow the regulation of specific nuclear protein phosphorylations, such as nucleolin phosphorylation during the G 1 /S transition.…”
Section: Figmentioning
confidence: 80%
“…Genetic studies showed that the kinase activity of CK2 is essential for viability of yeast (15). The involvement of CK2 in mitogenic signaling is strongly supported by approaches using microinjection of CK2 (16) or antibodies raised against CK2 (17,18). Moreover, several reports correlate an increase in CK2 activity with cell growth stimulation (reviewed in Ref.…”
mentioning
confidence: 99%
“…CKII activity has been reported to be induced by mitogenic stimulation in several systems (Sommercorn et al 1987;Karlund and Czech 1988;Ackerman and Osheroff 1989;Carroll and Marshak 1989), but this stimulation is relatively small (1.5-to 6-fold) and no concordant enhancement in the phosphorylation of a cellular substrate has been reported. On the other hand, the subcellular localization of CKII has recently been shown to differ though the cell cycle; in particular, the enzyme migrates out of the nucleus in S phase (Gauthier-Rouviere et al 1991;Yu et al 1991). This might suggest a model whereby Max DNA-binding activity that is present in quiescent cells is diminished following mitogenic stimulation by both CKII phosphorylation of Max and induction of Myc protein, and/or elevated in S phase when CKII activity in the nucleus is reduced and phosphatase PP2A activity rises ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SRF is required for both the induction of immediate early genes by growth factors and the induction of muscle-specific genes during differentiation. Microinjection of anti-SRF antibodies blocked the serum induction of the c-fos gene in NIH3T3 cells as well as the expression of musclespecific genes and the terminal differentiation of C2C12 skeletal myoblasts (9,10).…”
mentioning
confidence: 97%